Menyesap Makna : Analisis dan Kajian Sastra dalam Film Filosofi Kopi - Nadim Rafa; Aji Mulki Rabbani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The film Filosofi Kopi is a literary work that raises coffee as a metaphor, symbol, and narrative element of Coffee as part of global and local culture in Indonesia. This work not only offers interesting fictional stories, but also to analyze Tiwus copies from Java, using a qualitative approach with a method of analyzing literary texts that include thematic, stylistic, and intertextual aspects. This research seeks to understand how elements that have philosophical values that describe life, struggle, and social care. The results of the analysis show that the main themes of this are struggle, care and social interaction, which is reflected through a cup of coffee between the characters. Coffee is often presented as a representation of human relations, existence describes the daily dynamics in society, which connects existentialism, harmony, and reflection in life in a literary work. Presenting a diversity of meanings, starting from simple life symbols and human relationships. This research contributes to a deep understanding of how a cup of coffee can be raised into a theme and title that contains rich meaning and significance in the study of a literature